Construction of a Geobacter Strain With Exceptional Growth on Cathodes - Ueki, Toshiyuki; Nevin, Kelly P.; Woodard, Trevor L.; Aklujkar, Muktak A.; Holmes, Dawn E.; Lovley, Derek R. (Frontiers in Microbiology, 2018)
Insoluble extracellular electron donors are important sources of energy for anaerobic respiration in biogeochemical cycling and in diverse practical applications. The previous lack of a genetically tractable model microorganism that could be grown to high densities under anaerobic conditions in pure culture with an insoluble extracellular electron donor has stymied efforts to better understand this form of respiration. We report here on the design of a strain of Geobacter sulfurreducens, designated strain ACL, which grows as thick (ca. 35 µm) confluent biofilms on graphite cathodes poised at -500 mV (versus Ag/AgCl) with fumarate as the electron acceptor. Sustained maximum current consumption rates were > 0.8 A/m2, which is > 10-fold higher than the current consumption of the wild-type strain. The improved function on the cathode was achieved by introducing genes for an ATP-dependent citrate lyase, completing the complement of enzymes needed for a reverse TCA cycle for the synthesis of biosynthetic precursors from carbon dioxide. Strain ACL provides an important model organism for elucidating the mechanisms for effective anaerobic growth with an insoluble extracellular electron donor and may offer unique possibilities as a chassis for the introduction of synthetic metabolic pathways for the production of commodities with electrons derived from electrodes.